2008
DOI: 10.1007/s00540-008-0634-2
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of dexmedetomidine in a patient with herpetic stomatitis after living-donor lung transplantation

Abstract: A 31-year-old woman suffering from bronchiolitis obliterans received bilateral living-donor lung transplantation to treat end-stage respiratory failure. After 5 days' mechanical ventilation, the patient was successfully extubated. During mechanical ventilation, the patient was sedated with a continuous intravenous infusion of propofol and dexmedetomidine (DEX). To assuage postoperative pain, morphine was infused, first intravenously, then epidurally. The administration of DEX was continued after extubation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It is also reported that dexmedetomidine showed an analgesic effect in an ischemic, acute postoperative, and intractable cancer pain of human and herpetic stomatitis after living-donor lung transplantation (5-7). Moreover, dexmedetomidine exhibits antinociceptive actions on postoperative, streptozotocin-induced, complete Freund's adjuvant (CFA)-induced, formalin-induced, carrageenan-induced inflammatory, acute nociceptive, and neuropathic pain in various animal models (8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that dexmedetomidine showed an analgesic effect in an ischemic, acute postoperative, and intractable cancer pain of human and herpetic stomatitis after living-donor lung transplantation (5-7). Moreover, dexmedetomidine exhibits antinociceptive actions on postoperative, streptozotocin-induced, complete Freund's adjuvant (CFA)-induced, formalin-induced, carrageenan-induced inflammatory, acute nociceptive, and neuropathic pain in various animal models (8, 9).…”
Section: Introductionmentioning
confidence: 99%